Pengaruh Kualitas Pelayanan E-KTP Terhadap Kepuasaan Masyarakat Di Kabupaten Pulau Morotai Provinsi Maluku Utara - Ekklesia Hulahi; Ulung Pribadi; Syamsul Bahri Abd Rasyid; Sahrul Pora; Inrinofita Sari (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2022)
The government as a public service provider where the community must be responsible must be responsible and continue to strive to provide the best services to improve public services. For this reason, the government trains digital-based public services so that government agencies can serve the community easily and quickly. So, in this study, it aims to see the effect of e-KTP service quality on community satisfaction in Morotai Island Regency in North Maluku Province and this study uses quantitative methods to determine the quality of services that make the most impact on people's satisfaction. The sample drawn is 100 people. The data collection technique used is a survey technique, in which data is collected through the distribution of online questionnaires (Google forms). The results show that the evidence obtained from physical evidence, impact, strength, assurance and empathy has been applied in the effect of e-KTP services on community satisfaction carried out by the Ministry of Population and Civil Registration of Morotai Island Regency. There are two variables that have a positive and significant influence on other variables, namely service and empathy for community satisfaction in e-KTP. Meanwhile, three other variables that do not have significant variables are the capacity and guarantee of community satisfaction in the e-KTP service provided by the Morotai Island government. And to improve the quality of E-KTP services from the population and the Morotai Island Civil Registry Office to examine the variables that are at the center of this research, especially on variables that have a significant negative effect (physical evidence, arrests, and guaranteed), so they can comply with the rules and mechanisms in improving the quality of e-KTP services to the satisfaction of the community.